Shape Modelling and Volume Optimisation of Salt Caverns for Energy Storage - Katarzyna Cyran; Michal Kowalski (Applied Sciences, 2021)
Salt caverns are an attractive solution to the growing energy demand in view of their large storage capacity, safety of storage operation and long operation time. The designing process of salt caverns is still considered a complex issue despite progress in geotechnical, construction and exploration methods. Finding the optimal shape and dimensions of a salt cavern in given geological conditions is a difficult engineering problem in view of safety and stability requirements. In this paper, the stability of typical cavern shapes (cylindrical, enlarged top, and enlarged bottom), with each of the three variants differing by their diameter, was evaluated against the stability factors of the geological conditions of the bedded salt deposit. Moreover, the analysed shapes were examined in terms of edges. The three-step smoothing of sharp edges was performed, and its impact on the cavern’s stability performance was studied. Moreover, the analysis aimed to find the optimal cavern shape and volume in the implemented geological conditions. The evaluation was based on the following criteria: the displacement, effective strain, von Mises stress, strength/stress ratio and safety factor. The results of this evaluation can be useful in the design of an optimal cavern shape and volume and for planning new cavern fields for storing natural gas, compressed air or hydrogen in the bedded salt deposits.